The Water Footprint of Wine Production in Portugal: A Case Study on Vinho Verde - Leandro Adélcio Batista de Pina (2011)
The water footprint (WF) of a product is an indicator of the consumptive use of freshwater resources along the product life cycle. Water scarcity is recognised to be a large global problem. Therefore the calculation of the WF of agro-industrial products is important as they are widely known as having a significant footprint on water resources. The objective of this study was to calculate the WF of a very specific Portuguese wine: the vinho verde. The total WF is disaggregated into three components: green, blue and grey. The green WF refers to the consumption of rainwater stored in the soil. The blue WF refers to the consumptive use of surface and groundlevel freshwater. The grey WF measures the volume of freshwater needed to assimilate the pollutant load when considering current water quality standards.The WF is calculated for the activities taking place during the viticulture and the wine production process. The data, from 2009, were provided by a Portuguese company (Aveleda), that produces an important share (16%) of the national wine production. The total WF is calculated to be 463 liters of water per 0,75 liters of wine. The green and grey WF accounted for, respectively, 89% and 11% of the total WF. The green WF is exclusively associated with the viticulture and the grey WF is mainly caused during the wine production process.The blue WF is negligible because currently there is no irrigation during viticulture. The viticulture is responsible for about 91% of the total WF due mainly to the green water consumption. Therefore the WF of vinho verde depends mainly on the climate and soil conditions and crop properties. These are not controlled by the wine producing company. On conclude that a significant reduction of the WF may be achieved throughout the reduction of the pollutant load in the wastewater caused during the wine production phase. A sensitivity analysis was also carried out in order to evaluate the effects on the WF induced by changes in some input data.